2012
DOI: 10.1155/2012/981416
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Asymptomatic Carotid Disease and Cognitive Impairment: An Understated Link?

Abstract: Advanced carotid disease is known to be associated with symptomatic cerebrovascular diseases, such as stroke or transient ischemic attack (TIA), as well as with poststroke cognitive impairment. However, cognitive decline often occurs in patients with advanced carotid stenosis without clinically evident stroke or TIA, so it is also suspected to be an independent risk factor for dementia. Neurosonological methods enable simple and noninvasive assessment of carotid stenosis in patients at risk of advanced atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“… 9 Review articles are inconclusive on whether carotid stenosis leads to cognitive decline. 9 , 35 For example, declining cognitive function was associated with carotid plaque area but not luminal narrowing, 10 or carotid volume flow. 36 Removal of tight stenosis by carotid endarterectomy did not affect cognitive decline five years later.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Review articles are inconclusive on whether carotid stenosis leads to cognitive decline. 9 , 35 For example, declining cognitive function was associated with carotid plaque area but not luminal narrowing, 10 or carotid volume flow. 36 Removal of tight stenosis by carotid endarterectomy did not affect cognitive decline five years later.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe carotid disease without previous stroke or TIA can have subtle cognitive abnormalities that are undetectable by the MMSE and may only be identified by applying specific neuropsychological tests. 4 …”
Section: Evaluation Of Cognitive Functionmentioning
confidence: 99%
“…If asymptomatic advanced carotid stenosis indeed causes cognitive impairment, the decision on surgical treatment might consider cognitive evaluation using a neuropsychological test as a clinical definition of symptomatic carotid disease and may be considered as important as the effective treatment of vascular risk factors in stroke/TIA free patients with carotid stenosis. 4 …”
Section: Carotid Stenosis and Relationship With Cognitive Declinementioning
confidence: 99%
“…Cardiovascular disease and AD also share the same risk factors . Carotid artery and cardiovascular disease are the two major risk factors for AD . Some reports have indicated that patients with early onset AD had little cardiovascular damage, while patients with late‐onset AD exhibited evidence of ischemic damage to the left ventricular myocardium, and frequent heart valve damage …”
Section: Introductionmentioning
confidence: 99%